2011
DOI: 10.1007/s11739-011-0510-1
|View full text |Cite
|
Sign up to set email alerts
|

Allergy and psychologic evaluations of patients with multiple drug intolerance syndrome

Abstract: The multiple drug intolerance syndrome is a clinical entity characterized by adverse drug reactions to at least three drugs, chemically, pharmacologically and immunogenically unrelated, manifested upon three different occasions, and with negative allergy testing. Symptoms referred by the patients are often subjective, of neurovegetative origin. The aim of the study is to characterize patients suffering from the multiple drug intolerance syndrome from a psychological point of view, and to compare them to health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 9 publications
5
47
1
1
Order By: Relevance
“…Although De Pasquale et al [ 8 ] found an increased likelihood of somatisation in their MDIS cohort, we showed that rates of psychological comorbidities were similar between MDIS and non-MDIS patients. This disparity is likely to be caused by differences in methodology.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Although De Pasquale et al [ 8 ] found an increased likelihood of somatisation in their MDIS cohort, we showed that rates of psychological comorbidities were similar between MDIS and non-MDIS patients. This disparity is likely to be caused by differences in methodology.…”
Section: Discussioncontrasting
confidence: 83%
“…This disparity is likely to be caused by differences in methodology. We used physician-led diagnoses of psychological disorders, whereas De Pasquale et al [ 8 ] used psycho-diagnostic questionnaires to evaluate patients. Somatisation disorders have recently been identified as key risk factors for MDIS [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female sex has also been identified as a risk factor for MDAS . Prior studies have suggested associations between MDIS and/or MDAS and various psychiatric comorbidities, including anxiety, depression, alexithymia, and somatization . However, to date, no clear relationship is defined.…”
Section: Introductionmentioning
confidence: 99%
“…11 Patients with multiple drug intolerances also tend to have higher levels of anxiety, depression, and somatization. 12,13 Therefore, allergies may be associated with, or even serve as a surrogate for, Axis 1 disorders.…”
Section: Introductionmentioning
confidence: 99%